Optimizing Nitrogen Management in Food and Energy Production and Environmental Protection: Summary Statement from the Second International Nitrogen Conference - Ellis Cowling; James Galloway; Cari Furiness; Mary Barber; Ton Bresser; Ken Cassman; Jan Willem Erisman; Richard Haeuber; Robert Howarth; Jerry Melillo; William Moomaw; Arvin Mosier; et al. (The Scientific World Journal)
Human efforts to produce food and energy are changing the nitrogen (N) cycle of the Earth. Many of these changes are highly beneficial for humans, while others are detrimental to people and the environment. These changes transcend scientific disciplines, geographical boundaries, and political structures. They challenge the creative minds of natural and social scientists, economists, engineers, business leaders, and decision makers. The Second International Nitrogen Conference was designed to facilitate communications among all stakeholders in the “nitrogen community” of the world. The Conference participants’ goal in the years and decades ahead is to encourage every country to make optimal choices about N management in food production and consumption, energy production and use, and environmental protection. Scientific findings and recommendations for decision makers that emerged from the Conference are presented.